Losing Weight through Regular Exercise among Overweight/Obesity Women Aged 35-45 years - Yusni Yusni; Amiruddin Amiruddin; Razali Razali (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
Exercise is a simple and low-cost way to lose weight, but many people have become apprehensive to provide it. This activity aims to shift the community’s lifestyle from sedentary to active by encouraging physical activity through frequent gymnastics. Darussalam housewives gathered near the Universitas Syiah Kuala campus. There were two groups of 20 people: regular participants (n=11) and non-regular participants (n=9). Everyone in the study was between the ages of 30-45. Participants’ body weight (BW), height, and Body Mass Index (BMI) were measured before and after treatment. Participants did 60 minutes of gymnastics modiﬁed from Zumba, Aerobic, and Salsa, 3–4 times per week, at 05.00–06.00 p.m, for 12 weeks (3 months), and without any special diet. The regular group’s average age was 35.3 years, whereas the non-regular group’s average age was 36.78 years. The results showed that 80 percent and 22.22 percent of participants in the regular and non-regular groups, respectively, lost weight. Before and after exercise, the regular group’s mean BW decreased by 3.65 kg (68.25 and 84.6 vs. 59.19 and 59.25 kg), while the non-regular group’s BW increased by 0.06 kg. The regular exercise group’s BMI dropped by 1.53 kg/m2 after gymnastics (28.45 and 26.92 vs. 27.01 and 27.01 kg/m2), while the non-regular exercise group’s BMI remained unchanged. Gymnastic movements have been modiﬁed to include Zumba, Aerobics, and Salsa, which could reduce BW and BMI. As a result, sustained exercise is required to help people reduce their risk of obesity. This practice has helped the government of the Republic of Indonesia’s eﬀorts to increase physical activity and decrease the sedentary lifestyle in the population, thereby improving societal health. Obesity in women can be treated and prevented with regular exercise.